CMS Wordpress Based Academic Information System Design at SMPN 17 Marusu - Nahlah, Nahlah; Ruswandi Djalal, Muhammad (INTEK: Jurnal Penelitian, 2022)
School is one of the formal education facilities that must be able to provide the best services or facilities for students and also for parents. One of the right ways is to use information technology, namely accessing academic values through websites. The specific objective of this research is to produce an academic information system based on Wordpress Content Management System (CMS) that can be used by SMPN 17 Marusu in Maros Regency. The current website-based academic information system is made using a complex programming language and requires special skills to create the website. Wordpress is a platform for creating websites instantly. In this study, the information system was built using the prototype method so that it can be adapted to user needs. The resulting software is presented to the user, starting from the requirements analysis, design to implementation stage, and users are given the opportunity to provide input so that the resulting software really fits the user's needs. The prototype method consists of several stages, namely, requirements analysis, system analysis, system design, system testing, and system implementation. The design stage includes interface design, front end and back end using WordPress CMS. With this school website, it is hoped that it can help government programs in improving school performance and productivity.